Failure mechanism and control technology of soft-rock roadways subjected to high structural stress - Li, Mingjing; Ye, Lijin; Feng, Jihao; Fang, Yunmai; Wen, Haipo; Wu, Xiangbin (Frontiers in Earth Science, 2024)
The prevention and control of deformation and instability in high-stress soft rock roadways hold significant value for ensuring normal mine production and the safety of personnel and equipment. This study focuses on the pedestrian descent from the 11th mining area of the Yindonggou Mine, providing a thorough elucidation of the internal mechanisms leading to large deformation and instability in the roadway. It accounts for the influences of surrounding rock lithology, geological structure, and support measures. Consequently, based on the theory of rock instability, corresponding tunnel repair measures and control strategies were proposed and verified through field application. The results indicate that: (1) High strength dispersion and insufficient support resistance of the expansive weak and fractured surrounding rock sections are critical factors inducing significant deformation in the soft rock roadway of Yindonggou Mine. (2) The primary factor contributing to the large deformation disaster in the Yindonggou Mine roadway is the disturbance caused by proximate coal seam mining, which exacerbates the conflict between the high structural stress in the strata and the low strength of the surrounding rock. High-level stress initially leads to deformation in the weakly supported floor, followed by deformation and instability of the surrounding rock, ultimately culminating in the collapse of the entire roadway section. (3) Soft rock support should be designed with varying schemes tailored to the rock type and structural stress of the surrounding rock in the tunnel. For tunnels with carbon mudstone and expansive soft rock as the main roof and floor components, the support plan should primarily focus on enhancing the support stiffness of the tunnel wall. Conversely, for tunnels where sandstone predominates as the roof and floor material, the support plan should aim to restore the three-dimensional stress state of the surrounding rock and fully utilize its self-supporting capacity. (4) Based on the engineering conditions of pedestrian downhill in No.11 mining area of Yindonggou Mine, a differentiated support scheme is proposed. The feasibility and effectiveness of each support scheme are verified by numerical simulation, so as to provide valuable reference and enlightenment for similar projects.